2022
DOI: 10.1002/advs.202203395
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Neural Activity in the VLPO During Anesthesia and Sleep

Abstract: The invention of general anesthesia (GA) represents a significant advance in modern clinical practices. However, the exact mechanisms of GA are not entirely understood. Because of the multitude of similarities between GA and sleep, one intriguing hypothesis is that anesthesia may engage the sleep‐wake regulation circuits. Here, using fiber photometry and micro‐endoscopic imaging of Ca2+ signals at both population and single‐cell levels, it investigates how various anesthetics modulate the neural activity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…To quantitatively assess brain states during anesthesia, we utilized EEG and electromyography (EMG) recordings. The depth of anesthesia was evaluated based on the power ratio of the EEG signals within the delta (0.5–4 Hz) and theta (6–10 Hz) frequency bands, combined with the changes in the EMG ( Luo et al, 2023 ). Our results indicated that the administration of either KET or ISO elevated the EEG delta/theta power ratio while reducing EMG power ( Figure 1—figure supplement 1 ), suggesting that each drug induced a loss of consciousness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantitatively assess brain states during anesthesia, we utilized EEG and electromyography (EMG) recordings. The depth of anesthesia was evaluated based on the power ratio of the EEG signals within the delta (0.5–4 Hz) and theta (6–10 Hz) frequency bands, combined with the changes in the EMG ( Luo et al, 2023 ). Our results indicated that the administration of either KET or ISO elevated the EEG delta/theta power ratio while reducing EMG power ( Figure 1—figure supplement 1 ), suggesting that each drug induced a loss of consciousness.…”
Section: Resultsmentioning
confidence: 99%
“…EEG and EMG recordings were conducted as previously described ( Luo et al, 2023 ). Specifically, a stainless-steel electrode was positioned over the frontal cortex for EEG measurements, while an insulated EMG electrode was inserted into the neck muscles.…”
Section: Methodsmentioning
confidence: 99%
“…To quantitatively assess brain states across the four groups, we utilized electroencephalography (EEG) and electromyography (EMG) recordings (Figure 1—figure supplement 1). The depth of anesthesia was evaluated based on the power ratio of the EEG within the delta (0.5–4 Hz) and theta (6–10 Hz) frequency bands, combined with the changes in the EMG (Luo et al, 2023). Our findings showed that ISO and KET elevated EEG power ratio while reducing EMG power, suggesting both drugs induced a loss of consciousness.…”
Section: Resultsmentioning
confidence: 99%
“…All brains were sectioned to verify viral fluorescence expression, and placements of the optical fibers after the experiment was completed. Z‐scores transformed Ca 2+ signals were used to calculate the state of the PVH neurons 16,17 …”
Section: Methodsmentioning
confidence: 99%